Hydrothermal syntheses, crystal structures and photoluminescence properties of two lead-free perovskites - Ong, Yan Shing (2019)
Organic-inorganic metal halide perovskite is an emerging class of semiconductors. In recent years, there have been many breakthrough applications of this material, especially in the field of light emitting diodes, thin film solar cells and radiation detection materials. Photovoltaic (PV) technology; the conversion of solar energy to electricity directly have utilised hybrid halide perovskite solar cells (PSCs) and attaining a power conversion efficiency (PCE) of 3.8% back in 2009. Since then, it have improved tremendously to 22.1% in the past 8 years. [1] Perovskite nano-crystal scintillators used in radiation detection materials have shown superior traits compared to traditional bulk inorganic scintillators. [2] Lead halide perovskite also shows promises for lighting and display applications as its quantum dots (QDs) own colour‐tunable and narrow band emissions. [3] Perovskites have proven to be a compound with multiple constructive applications. However, lead is the major metal cation and 3D network corner-sharing for this group. Lead is a toxic element which will limit further applications as they are not only harmful to the environment, but to the human body as well. Therefore, there is a need for further research the possibilities of lead free halide perovskites to eliminate lead toxicity while retaining its unique characteristics. In this project, by introducing two multiimidazole molecules, tetrakis(imidazolyl)borate and tetrakis(N-imidazolemethylene)methane, as structure directing agents, two novel organic-inorganic hybrid bismuth-halide perovskites have been successfully prepared under hydrothermal conditions. The compounds were structural characterized by single-crystal X-ray diffractions, powder X-ray diffractions, infrared spectroscopy, thermolgravimetry measurement and ultraviolet-visible spectroscopy. What’s more, the photoluminescent properties of two compounds were studied.